Achieving a macroscopic Nondiffracting length from a microscopic All-fiber Bessel beam generator - Park, Junbum; Lee, Yong Soo; Oh, Kyunghwan (Elsevier BV, 2022)
The objectives: We carried out a thorough parametric analysis by varying the dimension of the fiber optic Bessel-beam generator (BBG) to obtain the maximum a macroscopic nondiffracting length (NDL). BBG consisted of a single mode fiber (SMF) and serially concatenated coreless silica fiber (CSF), where multimode interference took place to shape the incoming fundamental LP01 mode to the Bessel-like mode propagating in water. Methodology used: Focusing on three wavelengths lambda = 635 nm, 980 nm, and 1550 nm, we used the beam propagation method package for commercially available SMFs for each wavelength to find optimal CSF geometry. We also optimized the SMF parameters to increase the NDL further. Results obtained: Utilizing a simple all-fiber structure, we theoretically predicted that NDL in water reaching similar to 4 mm could be obtained from a microscopic fiber optic BBG. Their significance: This result can be readily applied to optical manipulation of biological substances in aqueous solutions and laser material processing and imaging.